Rib fracture fixation as a tool for extubation in a resource-poor environment. Issue 2 (9th February 2019) - Dickson-Lowe, Richard Alexander; Buitendag, Johannes Jacobus Petrus; Jolayemi, Olamide Oluwafunsho; Oosthuizen, George
Abstract : An elderly female with multiple comorbidities was involved in a pedestrian vehicle accident and sustained blunt chest trauma, arriving at a resource-poor hospital in rural South Africa. She had multiple bilateral rib fractures with a unilateral flail segment that caused her to develop respiratory failure. She was intubated and sent to the intensive care unit (ICU) for ventilation. She developed hospital and ventilator acquired pneumonia. She subsequently had hypoxic arrests on two separate occasions and two failed extubations. Despite inadequate access to provisions, this patient was taken to theatre for rib fracture fixation as an attempt to improve her lung function and get her off the ventilator. She was extubated two days after the procedure and discharged from ICU 4 days thereafter. On her follow-up, she reported that she had returned to normal daily living and tasks.